Geosystems Engineering - Geosystems Engineering (Taylor & Francis, 2026)
Geosystem Engineering comprehensively covers new developments in the field of mineral and energy resources engineering specially focusing on oil and natural gas exploration, analytical and economical geochemistry, geophysics, geology and applied geology, evaluation of the effects of mining activities, role of surface environment and impacts on human health, resource economics and policy, and related studies.
FI 0.4
Q3
Keywords: Engineering; Computing & Technology; Geoquímica; Geología aplicada; Acuerdos transformativos; Transformative agreements; Ingeniería de recursos minerales y energéticos; Exploración de petróleo y gas natural; Medio ambiente superficial.